(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study examines the impact of International Financial Reporting Standards (IFRS) andIndian Accounting Standards (Ind AS) adoption on the current ratio of leading Indian IT companies,namely Infosys, TCS, Wipro, Mindtree, and Rolta. Using a panel data approach, we analyze the currentratios under Indian GAAP, Ind AS, and IFRS during the period from FY10 to FY19. The results suggestthat the transition from Indian Generally Accepted Accounting Principles (GAAP) to IFRS and Ind AS hasled to a higher current ratio, indicating an improvement in liquidity position. This paper contributes tothe literature on the implications of accounting standard convergence and highlights the benefits ofadopting internationally recognized accounting standards in enhancing the quality of financial reportingand facilitating cross-border comparisons.